Election Night: Tom Bohigian Elected to Fresno City Council District #1 - Watkins, Howard::::::::: (1989)
Group photo of 30+ supporters: includes Craig Scharton, Cruz Bustamante, Bruce Bronzan, ?, Sheri Bohigian, and Tom Bohigian